STUDY OF THE COMPUTED TOMOGRAPHY MEASUREMENT OF DIAMETER OF ABDOMINAL AORTA IN NEPALESE - ARJUN, ACHARYA; DINESH, THAPA; GITA, CHALISE; SHARMA, PAUDEL (International Journal of Clinical and Biomedical Research, 2015)
Background: The diameter of abdominal aorta (DAA) has its own importance in human body in diagnosing several abdominal aortic diseases. Its size is the diagnostic parameter for the abdominal aortic aneurysm which is the localized dilation of the abdominal aorta. Methods: The DAA of Nepalese was measured according to age and sex at three different levels, just superior to the celiac axis, at renal pedicle level and just superior to bifurcation by using Computerized Tomography (CT) scan. Also the DAA of the normal people was compared to those having hypertension, alcohol consumption and smoking habit. Study Sample: Altogether, 125 patients were included who came to Tribhuvan University Teaching Hospital (TUTH), Maharajgung, Kathmandu, Nepal for abdominal CT scan. Among them 100 are normal population and 25 are the victim of hypertension, alcohol consumption and smoking habit. Results: The findings revealed that the DAA in most of the observed patients is less than the aneurysm limit i.e. smaller than 30mm except in one male patientof age 72 years. Conclusion: It is concluded that the diameter of abdominal aorta increases with ages and is pronounced more in Nepalese male population than in female. It is also higher in patients of both sexes having hypertension and smoking habit. KEYWORDS: Bifurcation; Celiac axis; CT scan, DAA; Renal pedicle level.